2020
DOI: 10.3390/antiox9100913
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Protective Effects of Tartary Buckwheat Flour Extracts against Ethanol-Induced Liver Injury in Rats

Abstract: The grains of Tartary buckwheat (Fagopyrum esculentum) are traditionally consumed on a daily basis and are used in the preparation of diverse processed foods owing to the high concentration of rutin, an antioxidant compound. However, rutin is highly concentrated in hull and bran, but not in edible flour fractions. Rutin-enriched TB flour extracts (TBFEs) were obtained by hydrothermal treatment (autoclaving, boiling, or steaming) and their pharmacokinetic profiles were evaluated following a single-dose oral adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…The activities of ALT, AST, and ALP are often used clinically as indicators to evaluate liver function, and their levels can reflect the degree of liver injury within a certain range [ 20 ]. In addition, anatomical observation and H&E staining can more directly reflect the development of liver tissue inflammation on mouse.…”
Section: Discussionmentioning
confidence: 99%
“…The activities of ALT, AST, and ALP are often used clinically as indicators to evaluate liver function, and their levels can reflect the degree of liver injury within a certain range [ 20 ]. In addition, anatomical observation and H&E staining can more directly reflect the development of liver tissue inflammation on mouse.…”
Section: Discussionmentioning
confidence: 99%
“…23 Recently, a rutin-enriched Tartary buckwheat extract prepared by hydrothermal treatment was also shown to exert potent anti-oxidant activity in a rat model of ALD. 16 Another study demonstrated that Tartary buckwheat extract prevented ALD by inhibiting the mitochondrial cell death pathway. 17 Despite the definite beneficial effect of Tartary buckwheat extract on ALD, the specific mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…15 Tartary buckwheat has been reported to protect against ALD, but the specific mechanism remains unclear. 16,17 Herein, we aimed to elucidate the beneficial effects of Tartary buckwheat extract in terms of lipid metabolism with the aid of lipidomic analysis. Our study aimed to provide more theoretical basis for its further exploitation as a medical plant or nutritional food.…”
Section: Introductionmentioning
confidence: 99%
“…Rutin also protects type 2 diabetic mice against liver injury [95]. The same function is seen for Tartary buckwheat grain extracts, through inhibition of mitochondrial cell death [96,97]. In vivo pharmacokinetics have also provided support for the administration of Tartary buckwheat extracts to prevent alcoholic liver disease in humans [98].…”
Section: Phenolic Substancesmentioning
confidence: 99%